Quick Response Code Indonesian Standard (QRIS) In Terms of Maqashid Sharia - Raditio Wahid; Muhammad Hanafi Zuardi (Jurnal Internasional Ekonomi Islam, 2023)
This research discusses technological developments in the economic field. Quick Response Code Indonesian Standard is a tool used to transact through digital technology, in the muamalah point of view, every development must be carried out a legal determination that can be used as a basis for its use. The determination method used in Islamic economics is Maqashid Sharia by weighing the benefits and harms in an object, therefore this study aims to analyze the use of Quick Response Code Indonesian Standard in review of Maqashid Sharia. This research uses qualitative methods with the type of library research that is analyzed maslahah mursalah. In this study it is known that the use of Quick Response Code Indonesian Standard (QRIS) contains benefits. These results are in line with the concept of maqashid sharia whose main goal is benefit, avoiding harm to all people, prioritizing the objectives of shara', not contradicting the Qur'an and sunnah.